Role of the WTO in Regulating World Trade in Medicinal Products and Equipment during the COVID-19 Pandemic - V. I. Teremetskyi; Y. V. Duliba (Law and Safety)
Peculiarities of international trade in medicinal products and equipment during the COVID-19 pandemic are considered.